What makes a graduate an agro-entrepreneur? - Ahmad, Siti Aznor; Lim, Hock Eam; Soon, Jan Jan (2014)
Realizing the importance of entrepreneurship to economic development, the Malaysian Ministry of Higher Education has launched the Higher Education Institute Entrepreneurship Development Policy in 2010. This because, based on the 2010 Graduate Tracer Study, there is a low involvement (5.5 percent) of graduates in entrepreneurship, compared to employment in other sectors.This warrants a study to explore the factors influencing a graduate to become agro-entrepreneur.This study aims to identify these factors and also the characteristics of what actually make an agro-based graduate entrepreneur. In-depth interviews are conducted with twelve graduate agro-based entrepreneurs.The entrepreneurs are also requested to rate the importance of various triggering factors which are identified by previous studies. The factor rating results reveals that relatively, the most important factors are interest, satisfaction of being an entrepreneur, a sense of contribution to the society, generic skills (leadership, problem-solving, creativity and innovation, analytical, time and group management), social networking and taking-up of entrepreneur courses (after completing undergraduate studies); whereas, formal entrepreneur education, either at the degree, diploma or certificate level, is the least important. Results of in-depth interviews reveal that the characteristics of a graduate agro-based entrepreneur include those such as the right attitude, open mindedness, willingness to learn and face challenges, diligence, and good social networking.